The 'obligatory passage point' in knowledge co-production: Italy's participatory environmental monitoring platform. - Minniti, Sergio; Magaudda, Paolo (Science as Culture, 2025)
The process of developing of a participatory environmental monitoring network in Italy, unfolded between 2013 and 2020, is analysed in order to explore the dynamics of knowledge co-production involving collaboration between scientists and non-experts, in the present case constituted by a community of weather amateurs and practitioners. Based on a qualitative approach and 15 in-depth interviews with different stakeholders involved in the early development of the pilot network, the analysis focuses on the dynamics of collaboration between the actors involved that led to the creation of the Italian participatory environmental monitoring platform. For the analysis, we adopt the theoretical model of 'translation' proposed by Michel Callon (1984), which focuses on the dynamics of the emergence of a network of collaboration between scientists and other heterogeneous actors. In particular, we focus on the notion of 'obligatory passage point' (OPP) along the translation process. Focusing on the process of translation and the dynamics that characterise the convergence towards a common OPP in the processes of network constitution and knowledge production highlights some crucial dynamics that support the unfolding of effective forms of participatory co-production, including: the understanding of how the roles and identities of different actors are recognised, transformed, productively aligned and consolidated; the performative power of participatory processes that are able to redefine and transform the pre-existing identities and roles of actors; and the outcome of the epistemic inclusion of practices and knowledge of less powerful actors within institutional, political and scientific frameworks.